The Evolving Concepts of Cancer Stem Cells in Head and Neck Squamous Cell Carcinoma. (21st January 2014) - Shah, Amit; Patel, Shilpa; Pathak, Jigna; Swain, Niharika; Kumar, Shwetha
Abstract : There is increasing evidence that the growth and spread of cancers is driven by a small subpopulation of cancer stem cells (CSCs)—the only cells that are capable of long-term self-renewal and generation of the phenotypically diverse tumor cell population. CSCs have been identified and isolated in a variety of human cancers including head and neck squamous cell carcinoma (HNSCC). The concept of cancer stem cells may have profound implications for our understanding of tumor biology and for the design of novel treatments targeted toward these cells. The present review is an attempt to conceptualize the role of CSCs in HNSCC—its implication in tumorigenesis and the possible additional approach in current treatment strategies.